Organizational Commitment : The role of Perceived Organizational Support and Workplace Spirituality - Musyaropah, Ulfah; Sari, Erita Yuliasesti Diah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Abstract Organizational commitment is important to owned by every member who is in an organization including a teacher. This study aims to examine the effect of perceived organizational support and workplace spirituality on teacher organizational commitment. Respondents in this study were 92 people from 123 population of permanent teachers who had at least one year's teaching experience. This study used a quantitative method with a multivariate correlation research design and multiple linear regression analysis techniques with the help of SPSS v.23. The results of the study show that simultaneously, there is a very significant influence between perceived organizational support and workplace spirituality on teacher organizational commitment. The contribution of perceived organizational support and workplace spirituality to organizational commitment is 55.6%. As for partially, perceived organizational support has a positive influence on organizational commitment with a contribution of 35.8% and workplace spirituality has a positive influence on organizational commitment with a contribution of 19.8%. The high organizational commitment possessed by teachers can occur due to the direct influence of fulfilling aspects of perceived organizational support and high spiritual workplace by the organization to its employees. It is important for organizations to pay attention to the welfare of teachers and think about the right way so that teachers always have a positive perception of the organization. The organization also helps teachers to be able to experience meaningful work so that teachers find harmony between personal values and organizational values. Keywords: Organizational commitment, Perceived organizational support, Workplace spirituality